Ichthyology - Lagler, Karl F. 1912-1985. 4 0 (Karl Frank),16; 5 (New York : Wiley, 1962)
This new and comprehensive treatment of the field of ichthyology, the first American effort in more than half a century, is intended as an introduction to the subject. It covers virtually every aspect of the science of fishes: how they are built; how they function; how they react to one another and to their environment; what principles govern their distribution; how characteristics are passed from parents to offspring; how they are classified, and how diverse and numerous they are; how they have evolved; and how they reproduce, feed, and grow. Considerable effort has been made by the authors to render Ichthyology useful to the reader lacking in the technical background. Scientific words are defined and scientific names of fishes are used throughout only in conjunction with English names. A large number of illustrations, many by the well known scientific illustrator, William Brudon, are included to help clarify the text -- Book Jacket.
1. Fish, animals, and man: what fish are -- Fish as ancestors to man -- Where fish live -- How fish live -- How and why fish are studied -- Opportunities in ichthyology -- 2. The major groups of fishes: scope of classification -- Aims of classification -- Method of classification -- Position of fishes among the chordates -- Major groups of living fishes -- Characterization of living fish groups -- Major groups of extinct fishes -- Relationships of the major groups of fishes -- List of common and representative families of living fishes -- 3. Basic fish anatomy: gross external anatomy -- Skeleton -- Muscles -- Gills and gas bladders -- Digestive tract -- Circulatory system -- Kidneys -- Reproductive glands-gonads -- Endocrine organs -- Nervous system -- 4. Skin: structure -- Squamation -- Barbels and flaps -- Coloration -- Light organs -- Poison glands -- 5. Foods, digestion, nutrition, and growth: natural food of fishes -- Feeding habits -- Digestion, absorption, and utilization of foods -- Nutrition of fishes -- Growth of fishes -- 6. Skeleton, build, and movement: skeleton -- Locomotion -- Body form and locomotion -- Fins and locomotion -- Body movement and swimming -- Myomeres and swimming -- Non-swimming locomotion -- Speed of travel -- Migrations -- 7. Blood and circulation: heart and circulatory vessels -- Blood, tissue fluids, and blood-forming organs -- Body temperature -- 8. Respiration: structure and function of gills -- Fish blood as a gas carrier -- Adaptions for air breathing among fishes -- The gas bladder -- 9. Excretion and osmotic regulation: osmoregulatory and excretory organs -- Endocrine control of excretion and osmoregulation -- 10. Reproduction: types of reproduction -- The reproductive system -- Spermatozoa and their formation -- Eggs and their formation -- Sex differences -- Sexual maturity -- Reproductive cycles -- Breeding -- Care of eggs and young -- Development -- 11. Integration: the role of the nervous and endocrine systems -- The nervous system -- The spinal cord -- The spinal nerves -- The autonomic nervous system -- Supporting tissues of the central nervous system -- Intelligence and behavior -- Endocrine organs -- The senses (sense organs) of fishes -- 12. Genetics and evolution: inheritance in fishes -- Hybridization -- Mechanisms of evolution -- Isolating mechanisms -- Parallel evolution or convergence -- Time rate of evolution -- 13. Systematics and nomenclature: introduction -- Suitability of fishes -- Historical background -- Tasks of the systematist -- Taxonomic concepts -- The data of classification -- Study collections -- Zoological nomenclature -- 14. Ecology and Zoogeography: definitions -- Water -- Organic productivity in aquatic ecosystems -- Ecological classifications of fishes -- Ecological factors -- Marine ecosystems -- Estuarine ecosystem -- Freshwater ecosystem -- Zoogeography -- Geography of freshwater fishes -- Geography of marine fishes -- Bipolarity.
Includes bibliographical references and indexes.
Keywords: 2 -- 0; 6; Fishes. -- 20; 20; 2